1999
DOI: 10.1038/sj.onc.1202700
|View full text |Cite
|
Sign up to set email alerts
|

NDF/heregulin-induced cell cycle changes and apoptosis in breast tumour cells: role of PI3 kinase and p38 MAP kinase pathways

Abstract: Neu dierentiation factor (NDF)/heregulin activates ErbB2 via heterodimerization with the NDF receptors ErbB3 and ErbB4. Cells which express normal levels of these receptors are often growth stimulated by NDF, whereas SKBR3, and other ErbB2-overexpressing breast tumour cells are growth inhibited. We demonstrate here that in SKBR3 cells, NDF induces G1 progression but also causes a G2 delay from day 1 and apoptosis from days 2 ± 3. G1 progression was associated with ErbB2 transactivation of ErbB3 and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 56 publications
6
83
0
Order By: Relevance
“…In other cell systems, delayed activation of the p38 MAP kinase pathway also has a negative impact on cell proliferation by inducing apoptosis (Daly et al, 1999;Takekawa et al, 2002;Bulavin and Fornace, 2004;Naito et al, 2004). Treatment of BT474 and SKBr3 cells with anti-HER2 antibodies for 72 h does not induce significant apoptosis (Le et al, 2003(Le et al, , 2005a.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell systems, delayed activation of the p38 MAP kinase pathway also has a negative impact on cell proliferation by inducing apoptosis (Daly et al, 1999;Takekawa et al, 2002;Bulavin and Fornace, 2004;Naito et al, 2004). Treatment of BT474 and SKBr3 cells with anti-HER2 antibodies for 72 h does not induce significant apoptosis (Le et al, 2003(Le et al, , 2005a.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that c-Myc protein levels ( Figure 6a) and mRNA levels ( Figure 6b, panel 1) decreased following scFv-5R induction. Similarly, when SKBr3 cells were treated with an ErbB2 inhibitor (PD153035) (Arteaga et al, 1997;Daly et al, 1999), a PI3 kinase inhibitor (LY294002) or a MEK1 inhibitor (PD 98059), each of the inhibitors caused a decrease in c-Myc mRNA levels ( Figure 6b, panels 2 and 3). The e ect of PD153035 was equivalent to 72 h of ErbB2 down-regulation (Figure 6b, panel 1 vs 3).…”
Section: C-myc Is Pivotal In Erbb2-mediated Proliferationmentioning
confidence: 90%
“…We next investigated the e ects of ErbB2 downregulation on the kinases ERK1/ERK2, Akt/PKB and p70 S6K that are stimulated in response to ErbB receptor activation Karunagaran et al, 1996;Daly et al, 1999). ERK1/ ERK2 were examined using an antiserum speci®c for the dually phosphorylated, active form of the kinases.…”
Section: Effects Of Erbb2 Down-regulation On Intracellular Signallingmentioning
confidence: 99%
“…209,[225][226][227] In ERBB2-over-expressing breast tumor cells, G1 progression after NRG stimulation was associated with ERBB2 transactivation of ERBB3 and stimulation of the PI3K pathway. 228 Contributions of ERBB3 and/or the ERBB2/ ERBB3 complex to these phenotypic effects of NRG has been confirmed by use of anti-ERBB2 or anti-ERBB3 antibodies 211,212,229 or of a dominant-negative ERBB3 construct. 230 The downstream participation of PI3K or pAKT was confirmed in some of these studies by use of pharmacological or dominant-negative inhibitors of PI3K 209 or by constitutively active constructs of the p110 catalytic subunit of PI3K and by pharmacological inhibition of AKT.…”
Section: Erbb3 In Normal and Neoplastic Tissues Cell Transformation Bmentioning
confidence: 92%